Penanaman Hortikultura Dengan Metode Vertikultur Di Desa Barejulat Kecamatan Jonggat, Lombok Tengah Untuk Memanfaatkan Lahan Pekarangan Rumah - Rohani; I Dewa Made Alit Karyawan; Hasyim; I Wayan Suteja; Made Mahendra (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Food is the most important basic need to sustain the life of all creatures, including humans. So it is necessary to strive for adequate and equitable fulfillment of needs. In addition to survival, food is very influential in improving the quality of life of the nation. Planting various vegetables for food availability in the household does not have to be supported by a large yard. The yard with a limited area can also be used as land for growing vegetables and fruits. The implementation of these activities sequentially consists of socialization, discussion, direct practice and mentoring. The results achieved from this program are increasing community awareness and skills through activities carried out with the community around Barejulat Village so as to encourage the community to be motivated to optimize the potential of resources in the form of yards owned by the community to increase. Welfare based on technology and local wisdom. At the same time, it teaches the community to understand how important it is to cultivate a passion for farming from an early age so that in the future the sustainable food house program can be continued by future generations.